The progress of research into pseudophosphatases - Liu, Deqiang; Zhang, Yiming; Fang, Hui; Yuan, Jinxiang; Ji, Lizhen (Frontiers in Public Health, 2022)
Pseudophosphatases are a class of phosphatases that mutate at the catalytically active site. They play important parts in many life processes and disorders, e.g., cell apoptosis, stress reaction, tumorigenesis, axon differentiation, Charcot-Marie-Tooth, and metabolic dysfunction. The present review considers the structures and action types of pseudophosphatases in four families, protein tyrosine phosphatases (PTPs), myotube protein phosphatases (MTMs), phosphatases and tensin homologues (PTENs) and dual specificity phosphatases (DUSPs), as well as their mechanisms in signaling and disease. We aimed to provide reference material for the research and treatment of related diseases.